2022
DOI: 10.1101/2022.02.01.478508
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-2 Immature Particle Morphology Provides Insights into Gag Lattice Stability and Virus Maturation

Abstract: Retrovirus immature particle morphology consists of a membrane enclosed, pleomorphic, spherical and incomplete lattice of Gag hexamers. Previously, we demonstrated that human immunodeficiency virus type 2 (HIV-2) immature particles possess a distinct and extensive Gag lattice morphology. To better understand the nature of the continuously curved hexagonal Gag lattice, we used single particle cryo-electron microscopy to determine the HIV-2 Gag lattice structure for immature virions. The reconstruction map reve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…All VLP lattices with various sizes and shapes were captured even with irregular shapes (Figure 7e and ), demonstrating TomoNet’s particle-picking ability on flexible lattices. Lattice defects on each VLP were also identified consistent with previous studies, 52 enhancing the understanding of lattice assembly mechanisms 53 Figure 7. Comparative visualization of lattices obtained from TomoNet and Relion tutorial.…”
Section: Resultssupporting
confidence: 85%
“…All VLP lattices with various sizes and shapes were captured even with irregular shapes (Figure 7e and ), demonstrating TomoNet’s particle-picking ability on flexible lattices. Lattice defects on each VLP were also identified consistent with previous studies, 52 enhancing the understanding of lattice assembly mechanisms 53 Figure 7. Comparative visualization of lattices obtained from TomoNet and Relion tutorial.…”
Section: Resultssupporting
confidence: 85%
“…Comparative studies probing residues within CA have identified many of the key interaction interfaces required for maintaining replication and morphology of HIV-1 (122,123), HIV-2 (124), and HTLV-1 (81), including those that dictate the formation of structural features such as the six-helix bundle of CA-SP1 and the two-and three-fold CA interfaces. Recent determination of the structure of the HIV-2 immature lattice demonstrates a similar hexameric organization to that of HIV-1 (125), further emphasizing the unique nature of HTLV-1 among human retroviruses.…”
Section: Morphological Diversity In Human Retrovirus Particlesmentioning
confidence: 99%